(3aj Xd GdeJZjQGJ GdEbJUGOjI GdYGdejI GdMGdjIs - (3eYjf Gejf(B, (3GdSjOs ((3YeGf(B:s (3O(B.(3f(B,s, 2010)
(3JYQja Yde GdGbJUGO h aQhYg , YdGbe Yde GdGbJUGO HGdYdhe GdGNQi , GdGbJUGO GdeYQaj , GdHWGdI , GdGSJKeGQ, GdJVNe , GdShb , GdJHGOd GdJLGQj h GdSjGSGJ GdJLGQjI , ejRGf GdeOahYGJ , UfOhb GdfbO GdOhdj , GdHfc GdOhdj ddEfTGA h GdJYejQ , GdJcJdGJ GdGbJUGOjI ,efXeI GdJLGQI GdYGdejI (B.s
(3eQGLY U(B.359s
Keywords: (3GdGbJUGOs; (3GdeJZjQGJ GdGbJUGOjIs; (3Yde GdGbJUGOs